An Efficient Methodology for Detecting the Vertical Movement of Structures - El-Ashmawy, Khalid L. A. (Engineering, Technology & Applied Science Research, 2023)
Details regarding the public safety of engineering structures can be gleaned from measurements and monitoring. The development of a methodology for monitoring and analyzing structures’ vertical displacement is explained in this paper. The developed methodology aims to add a new dimension to geometric leveling, and leveling routing, by applying a least squares solution for level network adjustment and performing statistical analysis to assess the change in vertical displacement. To monitor and analyze the vertical deformation of a building in Cairo, Egypt, the proposed methodology was utilized. Twenty monitoring points, five auxiliary points, and three local reference stations were utilized. All the measurements were taken with a geodetic invar staff and an automatic level with an attachment of a parallel plate micrometer. The observations were made for an interval of 81 months. The least squares adjustment technique was applied to obtain the adjusted levels and observations and to generate the required statistical data. The results of the subsequent epochs were compared to the results of the first epoch to determine the vertical movement of the monitoring points for each epoch. In addition, the significance of the present displacement was ascertained by comparing the values of vertical displacement to the determined 95% corresponding confidence intervals. The findings demonstrated that the building remained stable throughout the monitoring period. The case study demonstrates how effectively geometric leveling with least square adjustment can be used to monitor the vertical displacement of structures.